Epac1 increases myosin regulatory light-chain phosphorylation, energetic cost of contraction, and susceptibility to heart failure - Yoshiki Ohnuki; Kenji Suita; Misao Ishikawa; Yasumasa Mototani; Megumi Nariyama; Aiko Ito; Ichiro Matsuo; Yoshio Hayakawa; Akinaka Morii; Takao Mitsubayashi; Yasutake Saeki; Yoshihiro Ishikawa; et al. (PLoS ONE, 2025)
β-Adrenergic receptor (β-AR) stimulation of the heart, leading to increased cardiac output, is mediated by cyclic AMP (cAMP), which induces protein kinase A (PKA)-mediated phosphorylation of the myofilament proteins troponin I (TnI) and myosin binding protein-C (MyBP-C). The aim of this study was to investigate the contribution of the exchange protein activated by cAMP (Epac1), a PKA-independent cAMP effector, to the response of cardiac myofilaments to β-AR stimulation. The calcium sensitivity of force and ATPase activity, and the tension cost (ATPase activity/force) were significantly greater in skinned myocardium from transgenic mice specifically overexpressing Epac1 in the heart (Epac1TG) and wild-type (WT) mice treated with 8CPT-AM, an Epac-selective cAMP analogue, as compared with non-transgenic (NTG) or control mice, respectively. In addition, myosin regulatory light chain (RLC) phosphorylation was significantly greater in Epac1TG and WT mice treated with 8CPT-AM than in NTG or control mice via phospholipase C/phosphokinase C, without any change in the phosphorylation of TnI or MyBP-C. We also examined the effects of chronic β-AR stimulation on cardiac function in Epac1TG. The left ventricular ejection fraction was significantly decreased from baseline in both NTG and Epac1TG after isoproterenol infusion (60 mg/kg/day for 1 week), but the magnitude of the decrease was much greater in Epac1TG. Our results suggest that Epac1 activation might induce an imbalance between force-generating capacity and ATPase activity in skinned myocardium. This could increase oxygen consumption and the energetic cost of contraction in living myocardium under conditions of chronic β-AR stimulation, leading to the development of heart failure.